2019
DOI: 10.1098/rsos.181840
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous conversion of O -tosylates of 2-(piperazin-1-yl)ethanols into chlorides during classical tosylation procedure

Abstract: A direct conversion of piperazinyl ethanols into chlorides via a classical O -tosylation protocol is observed. The acceleration of the transformation by the piperazine unit is demonstrated. It is found that the reaction goes via the corresponding O -tosylate, which converts spontaneously into chloride with different rate depending on the substrate structure. In the case of pirlindole derivative, partially aromatized chloride formation was observed upon prolongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Among the latter, the constrained 1‐phenylethylamine analogues 1‐aminoindane and 1,2,3,4‐tetrahydro‐1‐naphthylamine were chosen with the idea to restrict partially the flexibility of 1‐phenylethyl unit by connecting methyl and phenyl groups in a cyclic element. The best selectivities in our previous investigations were achieved by using aldehydes with oxygen‐containing substituents, and it was found that the selectivity is dependent on the number and position of the latter . Therefore, the efficiency of a series of aromatic aldehydes possessing one, two, or three methoxyl groups was studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the latter, the constrained 1‐phenylethylamine analogues 1‐aminoindane and 1,2,3,4‐tetrahydro‐1‐naphthylamine were chosen with the idea to restrict partially the flexibility of 1‐phenylethyl unit by connecting methyl and phenyl groups in a cyclic element. The best selectivities in our previous investigations were achieved by using aldehydes with oxygen‐containing substituents, and it was found that the selectivity is dependent on the number and position of the latter . Therefore, the efficiency of a series of aromatic aldehydes possessing one, two, or three methoxyl groups was studied.…”
Section: Resultsmentioning
confidence: 99%
“…Among the latter, chiral ketene precursors are the most widely applied, while the records in the literature on the efficiency of chiral amines are quite limited. Recently, we reported on the enantioselective trans ‐β‐lactam synthesis driven by chiral 1‐phenylethyl or regioisomeric naphthylethyl amines. Promising selectivities were achieved, up to 54%, and therefore, further variations in the auxiliary structure were justified.…”
Section: Introductionmentioning
confidence: 99%
“…These products have potential applications in various fields due to their improved solubility and biological activity compared to the parent compound. Sulfonate esters appear as suitable starting compounds in the activation of the hydroxy group, [23,24] in many coupling reactions, [25][26][27] in the production of sulfonamides [27][28][29][30] which are synthetic antibiotics used as antibacterial agents. Along with this versatile use, it is of great interest to researchers to develop many new methods for the production of sulfonate esters, [21,28,[35][36][37][38][39] which possess important biological activity such as anticancer, [19,40] antibacterial, [18,35,41] some enzyme inhibitory, [20,42,43] anti-viral, [21] insecticidal activities.…”
Section: Inhibition Studiesmentioning
confidence: 99%
“…The synthesis of sulfonate esters from 3-hydroxyflavone typically involves the activation of the hydroxyl group on the 3position of the flavone ring, [23,24] followed by sulfonation and deprotection to produce the sulfonate ester product. [25][26][27] The product is usually isolated and purified using chromatography or recrystallization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…After removing the solvent under reduced pressure, the crude product was recrystallized (PE/EA 1:1) to give 57% of the product 28 (0.163 g; 0.397 mmol). Synthesis of 7-chloro-4-(piperazine-1-yl)-quinoline (15) 37 4,7-Dichloroquinoline (5.28 g; 26.6 mmol; 1 eq.) and piperazine (3.44 g: 40.0 mmol; 1.5 eq.)…”
Section: Synthesis Of 1-(2-fluoroethoxy)-4-methoxybenzene (21) 32mentioning
confidence: 99%